Throughfall quantity and carbon input beneath canopy gaps of varying size in degraded tropical peatland forest of West Kalimantan, Indonesia - DWI ASTIANI; LISA M. CURRAN; MUJIMAN MUJIMAN; RUSPITA SALIM (Biodiversitas Journal of Biological Diversity, 2017)
Astiani D, Curran Lm, Mujiman, Salim R. 2017. Throughfall quantity and carbon input beneath canopy gaps of varying size in degraded tropical peatland forest of West Kalimantan, Indonesia. Biodiversitas 18: 1258-1264. Tropical peatland forest ecology, is mostly determined by peatland hydrological conditions. However, deforestation, forest degradation, or any other environmental disturbance can transform hydrological patterns and processes for peatland water movement, and thus alter carbon flow via water in this type of ecosystem. These changes arise from alteration in the quantity of throughfall (water that falls through plant canopies), in its interception, and in its evaporation to the atmosphere from vegetation surfaces. We have investigated the effects of a gradient of forest degradation levels, represented by canopy gaps (open, intermediate and closed), on throughfall quantity to the peatland forest floor. Nine plots, 50m x 50m in size, were stratified into the three forest canopy gap classes. Nine bucket collectors were used for throughfall, and tipping bucket rain gauges were set up for precipitation monitoring. Results show that annual precipitation in the area was 3,168.8 Â± 111.3 mm, with a mean monthly rainfall of 264.0 Â± 15.3 mm. Throughfall monitoring demonstrated that closed canopies transferred significantly more water as throughfall than intermediate or open canopies, due to differences in their effect on water movement through the canopies. The proportion of precipitation that passed through the canopies to the forest floor as throughfall was measured to be 76.5%, 77.3% and 89.4 %, or 202, 204 and 236 mm per month, respectively for open, intermediate, and closed canopies. It was found that higher levels of canopy cover resulted in significantly higher amounts of total organic carbon (TOC) content per unit of throughfall; specifically, 2.5 2.8 and 3.4 mg L-1 respectively for the open, intermediate, and closed canopies. When coupled with the higher quantity of throughfall in the closed canopy, the higher concentration of carbon results in a greater amount of carbon brought to the peatland forest floor by the throughfall pathway. This could also have impacts for other nutrients in the peatland soil.